Modular injection mould with a conformal cooling channel for the production of hydraulic filter housings - Zacharski, Andrzej; Samborski, Tomasz; Zbrowski, Andrzej; Kozioł, Stanisław; Poszwa, Przemysław (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2023)
The article presents the idea, design, construction, and implementation of a production technology for hydraulic filter housings using a modular injection mould. The annual demand for filters for specialised marine hydraulics systems by HYDROMEGA averages about 1,000 pieces. Two sizes of filters with the same housing connection dimensions are used. Due to the small scale of production, the modular injection mould was designed and manufactured to press two types of a polyamide housing. Changing the shape of a moulded part requires removing or installing modules that change the die and punch dimensions, which reduces the costs of production of a single tool compared to the costs of production of two separate tools. The mould design process was supported by the numerical analyses of operation and processes of plastic injection, cooling, moulded part shrinkage, and mould cavity deaeration. A mould and a series of moulded parts were manufactured and verified positively for dimensions and durability.